Grief and Posttraumatic Growth in Individuals Who Have Experienced the Death of a Loved One From Six Latin American Countries: The Moderating Role of Gender and Age (2025)
This study assessed the relationship between grief and posttraumatic growth (PTG) in 2415 individuals from six Latin American countries, and how the relationship between these variables is moderated by gender and age. The Posttraumatic Growth Inventory-Short Form and Pandemic Grief Scale were used. Moderation analysis utilized Model 2, proposed by Hayes. The findings from the analysis indicate that the proposed regression model is statistically significant in most countries. Gender moderated the relationship between grief and PTG in El Salvador and Peru; meanwhile, age moderated this relationship in Uruguay. The findings support the importance of incorporating gender and age differences into both the theory of grief and PTG and empirical studies investigating these variables in Latin America. Furthermore, mental health professionals should consider gender and age differences when planning interventions aimed at fostering PTG in individuals who have experienced the loss of a loved one in the evaluated countries.